Informed consent in a tuberculosis genetic study in Cameroon: information overload, situational vulnerability and diagnostic misconception. (October 2022) - Mohammed-Ali, Ali Ibrahim; Gebremeskel, Eyoab Iyasu; Yenshu, Emmanuel; Nji, Theobald; Ntabe, Apungwa Cornelius; Wanji, Samuel; Tangwa, Godfrey B; Munung, Nchangwi Syntia
Concerns around comprehension and recall of consent information by research participants have typically been associated with low health and research literacy levels. In genomics research, this concern is heightened as the scientific and ethical complexities of genetics research, such as biobanking, genetic susceptibility, data sharing, and incidental findings may be more difficult for potential research participants to understand. However, challenges to research participants' comprehension of consent information may be compounded by factors beyond health and research literacy levels. To identify factors that may impact research participants' understanding and recall of consent information, we designed a qualitative study to explore whether participants enrolled in a tuberculosis genetics study (TBGEN-Africa) in Cameroon understood the objectives of the study, the risks and benefits and certain key aspects of the study such as biobanking and data sharing. The results showed that research participants had limited understanding and/or recall of the TBGEN-Africa study goals and methods. Some participants were of the opinion that TBGEN-Africa was not a genetics study because tuberculosis is not an inheritable condition. Factors that may have hindered understanding and/or recall of study information are diagnostic misconception (research participants consider research as part of medical diagnosis), and information overload and situational vulnerability (consent at a time of physical and emotional distress). There is a need for improved practices to support research participants' understanding of consent information in genetics studies including designing the consent process in ways that minimize psychological distress and diagnostic/therapeutic misconception.